Dengue Infections Among Household Contacts of Symptomatic Index Cases: Implications for Community-Based Intervention Studies - Erik Koehne; Liesbeth Van Wesenbeeck; Martin L. Hibberd; Annemie Buelens; Michiko Toizumi; Kim De Clerck; Leen Vijgen; Ole Lagatie; Lucy Masdin; Hien Anh Thi Nguyen; Hoang Huy Le; Duc Anh Dang; et al. (Viruses)
Background: Dengue is a global health concern, with half of the world’s population at risk and no antiviral treatment available. This Phase 0 study investigated dengue infections among household contacts (HHCs) of dengue index cases (ICs) and assessed the feasibility of conducting a Phase 2 trial for a novel antiviral. Methods: Participants were enrolled in Nha Trang, Vietnam, from April 2022 to February 2023. Dengue ICs were identified within 72 h of fever onset, and their healthy adult HHCs enrolled within 48 h. Blood samples and questionnaires were collected bi-weekly for four weeks, with a follow-up visit on day 40. DENV RT-qPCR, NS1, and anti-DENV IgM/IgG ELISAs were performed. Results: Overall, 130 dengue ICs and 301 HHCs were enrolled, with 91.7% (276/301) completing all follow-up visits. Baseline anti-DENV IgG showed prior dengue infections in 262/301 HHCs (87.0%). Fifty HHCs were excluded from the HHC infection analysis based on evidence of a DENV infection (viral load [VL], NS1, IgM, and IgG results) at enrollment. During follow-up, 2.0% of HHCs (5/251) had DENV infections based on virological parameters (DENV RNA and/or NS1 positivity), and anti-DENV IgG/IgM seroconversion was detected in 7.2% (18/251). Conclusions: This study demonstrated the operational feasibility of a dengue IC-HHC design for a Phase 2 trial.